Financial risk exposures of the airlines industry: evidence from Cathay Pacific Airways and China Airlines - Yashodha, Yasmin; Abdul Hamid, Baharom; Habibullah, Muzafar Shah (Faculty of Economics and Business, Universiti Malaysia Sarawak, 2016)
This study explores the long run and dynamic relationships between the stock price of Cathay Pacific Airways and China Airlines against key determinants of financial risks exposure confronting the airline industry, which include interest-rate, exchange rate and fuel price risk exposures for the period of January 1996 to December 2011. The (Johansen & Juselius, 1990)cointegration technique was employed to detect any long time trending relationship followed Vector Error Correction Model (VECM) and Vector Auto-Regression (VAR). The generalised forecast error variance decomposition and the generalised impulse response function were employed to comprehend the effects of theses financial risk exposures. Our empirical results suggest that exchange rate movements have a substantial impact, compared to the fuel price and interest rate exposures against the stock price of the analysed airline. Our findings play a pertinent role in the determination of the respective airlines foreign vulnerability and financial policies which would be helpful for industry players and policy makers from a financial stability perspective.